Advancing Metaverse E-Commerce: A Quantitative Data Analysis Study on the Usage of AI in Virtual Shopping and Live Commerce - V, Sujit (Digital Repository of Theses, 2025)
This dissertation aims to analyze one of the most significant and continuously evolving areas in the modern world of commerce – the Metaverse and its significant aspects, focusing on virtual shopping and live commerce. Over time, the digital environment has grown, leading to businesses incorporating sophisticated technologies such as virtual reality and artificial intelligence. These technologies are helpful when designing new means to provide customers with enhanced and individualized buying experiences. The research aims to pinpoint what these innovations are doing to consumers' behavior, expectations, and the landscape of the retail environment. It is for this reason that the study commences with the early backgrounds and evolution of the eCommerce business, from simple websites that were merely virtual shops to the current highly developed systems that encompass multiple features and capabilities. It vii defines the significant events that have formed the contemporary context of online shopping and considers how these events have affected customers. Particular emphasis is placed on virtual shopping and live commerce and the conditions that facilitated the launch of these activities and techniques. Quantitatively, the research evaluates the critical changes in consumers' expectations and satisfaction levels after incorporating AI and virtual shopping technologies. The studies present the type of response that consumers have received regarding these technologies and how these technologies are perceived, and the results shown are that while these technologies go a long way in providing convenient and personalized solutions, there is still the reality that there must be a considerable gap on those with awareness of such sophisticated facilities. This gap sometimes leads to different satisfaction levels due to the effectiveness of implementing these technologies and passing information to consumers. The dissertation also takes time to explain some of the problems the conventional eCommerce industry faces, such as too much competition and constantly evolving consumer views on what constitutes practical eCommerce. It elaborates on how social aspects of live commerce within the Metaverse improve the shopping experience and consumer behavior. Besides, the studies describe live commerce's effectiveness in increasing sales conversion, customer retention, and building brand loyalty.